On Application of Optimal Multihypothesis Tests for the Bounds Construction for the Increase of Growth Rate of Stock Market - Haroutunian, Evgueni A.; Martirosyan, Artak R.; Yessayan, Aram O. (Mathematical Problems of Computer Science, 2021)
In the present paper new bounds for increase of the growth rate of stock market (when an erroneous probability distribution is used) are obtained applying the matrix of reliabilities of optimal tests.